1993
DOI: 10.1104/pp.101.3.759
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the le Mutation in Young Ovaries of Pisum sativum and Its Effect on Fruit Development

Abstract: l h e effect of the /e mutation on the growth and gibberellin (CA) content of developing fruits was investigated using the near-isogenic lines of fisum sativum L. 205+ (LeLe) and 205-(/ele). Although stem elongation is known to be reduced in 205-plants by approximately 65%, the growth of pods and seeds was unaffected by the /e mutation. CAI, CA,, and CAZo stimulated parthenocarpic development of unpollinated ovaries on both 205+ and 205-plants. GA2, was less active on 205-ovaries than on 205+, whereas CAI had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
2
22
0
Order By: Relevance
“…Comparison of nearisogenic lines of pea that contain either the wild-type PsGA3ox1 gene (LELE) or a 1-bp point mutation of LE that greatly increases the K m of the encoded GA 3-oxidase (lele) demonstrated that the mutation (lele genotype) reduced GA 1 content and growth of internodes (Ross et al, 1992). The content of GA 1 was also lower (seven to 10 times) in young lele pericarps compared with those of LELE, but only minor effects on fruit growth were observed (Santes et al, 1993; MacKenzie-Hose et al, 1998). In order to determine the minimum amount of bioactive GA necessary for pea fruit set and growth, the size of the pericarp was plotted against the GA 1 concentration in nonpollinated fruit growing after application of GA 1 or GA 3 to the leaf subtending the fruit (Rodrigo et al, 1997).…”
Section: Auxin (4-cl-iaa) Regulates Ga Biosynthesis and Catabolism Inmentioning
confidence: 96%
See 1 more Smart Citation
“…Comparison of nearisogenic lines of pea that contain either the wild-type PsGA3ox1 gene (LELE) or a 1-bp point mutation of LE that greatly increases the K m of the encoded GA 3-oxidase (lele) demonstrated that the mutation (lele genotype) reduced GA 1 content and growth of internodes (Ross et al, 1992). The content of GA 1 was also lower (seven to 10 times) in young lele pericarps compared with those of LELE, but only minor effects on fruit growth were observed (Santes et al, 1993; MacKenzie-Hose et al, 1998). In order to determine the minimum amount of bioactive GA necessary for pea fruit set and growth, the size of the pericarp was plotted against the GA 1 concentration in nonpollinated fruit growing after application of GA 1 or GA 3 to the leaf subtending the fruit (Rodrigo et al, 1997).…”
Section: Auxin (4-cl-iaa) Regulates Ga Biosynthesis and Catabolism Inmentioning
confidence: 96%
“…Higher concentrations of GA 1 in the pericarp (20 ng g 21 fresh weight) did not result in substantial further growth. Therefore, the concentration of GA 1 in young lele pods (0.1 ng g 21 fresh weight at 6 DAA; Santes et al, 1993) may be sufficient, if not optimal, to stimulate fruit set and growth in this tissue.…”
Section: Auxin (4-cl-iaa) Regulates Ga Biosynthesis and Catabolism Inmentioning
confidence: 99%
“…Although GA 1 concentration was lower in young seeds (2.7 times) and pericarps (seven times) of lele, compared with levels in LELE at 6 d after anthesis (DAA), the growth of pods (in length) and seeds (in weight) was not affected by the le mutation. However, the levels of GA 20 and GA 29 were substantially elevated in lele compared with LELE in both tissues (Santes et al, 1993). These results suggest that 3b-hydroxylation of GA 20 to GA 1 is reduced in pericarps and seeds by the le mutation, even though it did not affect the general fruit phenotype, bringing into question a possible causal role of PsGA3ox1 (LE) in the production of GA 1 during fruit development in pea.…”
Section: Transgenic Psga3ox1 Overexpression Increases Pericarp Lengthmentioning
confidence: 80%
“…Santes et al (1993) investigated the effect of the le mutation on the growth and GA content of developing fruits in near-isogenic lines of pea, lines 205 + (LELE; PsGA3ox1) and 205 2 (lele). Although GA 1 concentration was lower in young seeds (2.7 times) and pericarps (seven times) of lele, compared with levels in LELE at 6 d after anthesis (DAA), the growth of pods (in length) and seeds (in weight) was not affected by the le mutation.…”
Section: Transgenic Psga3ox1 Overexpression Increases Pericarp Lengthmentioning
confidence: 99%
See 1 more Smart Citation